Gas temperature of diffuse negative corona discharge - Bolotov, O.V.; Golota, V.I.; Gurtovoi, S.D.; Sitnikova, Yu.V.; Moshinskii, D.V. (Вопросы атомной науки и техники, 2013)
The emission spectra of the second positive system of nitrogen for the diffuse negative corona discharge in ambient air were studied. The rotational structure of spectral lines was analyzed and the spectra were identified. The calculations, using the model of non-rigid rotor was made. The rotational temperature of nitrogen molecules was specified. The dependence of rotational temperature on the applied voltage as well as on the discharge operation mode was shown.